In vivo functional screening on innate immunity of lactic acid bacteria in Galleria mellonella preclinical model: comparative analysis of Lactiplantibacillus plantarum and Lentilactobacillus kefiri - Guarnieri, Antonio; Falcone, Marilina; Brancazio, Natasha; Mukhtar, Farwa; Worku, Addis Temie; Cutuli, Marco Alfio; Iacovino, Vincenzo Pio; Ganassi, Sonia; De Cristofaro, Antonio; Di Marco, Roberto; Petronio Petronio, Giulio (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionAmong probiotics, Lactic Acid Bacteria modulate host immunity via strain-specific molecular patterns. The invertebrate model Galleria mellonella offers conserved innate immune pathways and is increasingly applied for preclinical screening of probiotic functions.MethodsWe evaluated the immunomodulatory activity of Lactiplantibacillus plantarum ATCC 14917 and Lentilactobacillus kefiri DSM 10551 in G. mellonella. Larvae were injected with 106 CFU/larva of each strain, and survival and health indices were monitored for 72 h. The temporal transcriptional response of ten innate immunity-related genes, including Toll and IMD signalling, Toll receptor, cytokine-like ligand, and antimicrobial effectors, was assessed via qRT-PCR over 3–24 hours, complemented by correlation and hierarchical clustering to identify co-expression modules and strain-specific transcriptional patterns.ResultsBoth strains were non-toxic and induced strain-dependent gene expression patterns. L. plantarum induced a stronger and more sustained activation of immune signalling pathways and effector responses, whereas L. kefiri was characterised by an earlier and prolonged activation of stress-related and tissue-protective mechanisms. Correlation and clustering analyses revealed distinct co-expression modules that reflect modulation of the Toll and IMD pathways.DiscussionThese findings suggest that G. mellonella could serve as a cost-effective in vivo model for functional screening of Lactobacillus spp. with immunomodulatory potential and possible translational relevance to human innate immunity.